A Narrative Inquiry into the Process of Inferential Identity upon Multiracial Children. (April 2023) - Chin, Philippa; Nambiar, Aishwarya
The authors highlight the experiences of monoracial parents of multiracial children in characterizing and inferring their child's ethnic and racial identity in the home. A review of existing research reveals the scarcity of frameworks that provide a model to help monoracial parents in this process. A narrative inquiry is utilized to explore how these parents racially and ethnically identify their multiracial children and the results are discussed. A detailed discussion inclusive of the limitations and implications for clinical practice and future research is noted.